1987
DOI: 10.1002/pssb.2221410102
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties of Carbides, Nitrides, and Oxides of Subgroup VIa Transition Metals. Theory and Experiment

Abstract: Contents

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 89 publications
1
2
0
Order By: Relevance
“…3 the p-d orbital projected and total DOS plots exhibit a high degree of hybridization between the carbon p orbital and the chromium d orbital around the Fermi level. This characteristic was previously observed for TMC, nitrides and sulfides [7,12,28] with different crystalline structures, i.e., the presence of the nonmetal atom promotes the hybridization regardless of the crystalline phase. Our results also show that hybridized states yield a multi-peak structure in the DOS curve and that the Fermi level is located in the region of metallic states.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…3 the p-d orbital projected and total DOS plots exhibit a high degree of hybridization between the carbon p orbital and the chromium d orbital around the Fermi level. This characteristic was previously observed for TMC, nitrides and sulfides [7,12,28] with different crystalline structures, i.e., the presence of the nonmetal atom promotes the hybridization regardless of the crystalline phase. Our results also show that hybridized states yield a multi-peak structure in the DOS curve and that the Fermi level is located in the region of metallic states.…”
Section: Resultssupporting
confidence: 54%
“…NaCl-type structure compounds from the fourth and fifth group TMC have been the subject of extensive investigations on the electronic structure, and some similarities were found for this class of compounds such as the overlap between valence and conduction bands [9,10] and a strong hybridization of the non-metal p orbitals and the metal d orbitals [10,11,18]. It was also observed that compounds having two different crystal structures with the same metal, exhibit a sharp difference in the band structure [12]. This fact is reflected in the catalytic properties and much effort was done to quantitatively assess that the lattice structure has an important role on activity and selectivity for certain catalytic processes [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation